Factors Associated with the Quality of Work Life in Doctors at Hospitals in Loja - Astudillo-Romero, Xavier; Urgilés-Barahona, Cristina Elisabeth; Cabrera Celi, Stefanny Daniela; Sotomayor-Quizhpe, Gabriela; Salinas-Rivera, Guido (Journal of Posthumanism, 2025)
Stress, work overload, and organizational climate affect the performance of healthcare personnel and hinder work environment improvement. This study aimed to identify factors associated with the perception of quality of work life (QOL) in hospitals in southern Ecuador. A quantitative, analytical, and cross-sectional study was conducted with 134 physicians, using the short version of the QOL-GOHISALO questionnaire to assess QOL. Perceptions of QOL were found to be low (mean: 80.87 ± 17.56), in contrast to the theoretical mean. Significant differences were found based on academic level, work schedule, psychological and/or neurological disorders, self-perceived health, and parenting. The QOL of healthcare personnel is low and is influenced by sociodemographic, occupational, family, and health factors.